1992
DOI: 10.1029/92gl02101
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of electromagnetic waves from a plasma: Enhanced ion acoustic fluctuations due to ion‐ion two‐stream instabilities

Abstract: Observations by the ElSCAT and Millstone Hill radars of strongly enhanced, often asymetric, ion acoustic line spectra in the topside auroral ionosphere have been reported recently by a number of researchers. Such strongly enhanced ion acoustic line spectra are shown to arise naturally in a plasma unstable to the ion‐ion two‐stream instability. A linear theory of density fluctuations is used for the calculations, which should be applicable to weakly unstable non‐magnetized plasmas near the onset threshold of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 16 publications
1
52
0
Order By: Relevance
“…This questions the idea that two enhanced shoulders ever coexist on one magnetic field line and deals therefore with the objection of Wahlund et al [1992a] to electron ionacoustic instabilities being the cause of the enhanced radar spectra. Two-stream instabilities do not require the very high current densities needed to explain the spectra in terms of electron ion-acoustic instabilities, but they do require that the ion drift velocity be of the order of its thermal velocity.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This questions the idea that two enhanced shoulders ever coexist on one magnetic field line and deals therefore with the objection of Wahlund et al [1992a] to electron ionacoustic instabilities being the cause of the enhanced radar spectra. Two-stream instabilities do not require the very high current densities needed to explain the spectra in terms of electron ion-acoustic instabilities, but they do require that the ion drift velocity be of the order of its thermal velocity.…”
Section: Observationsmentioning
confidence: 99%
“…St.-Maurice et al [ 1996] discuss the inferred field-aligned currents in terms of intense parallel electric fields of up to a few hundred microvolts per meter in magnitude together with horizontal scales of a few hundred meters or less. Forme [1993] has suggested that ion-acoustic fluctuations may be due to parametric decay of Langmuir waves, and Wahlund et al [1992a] propose a theory based on ion-ion two-stream instabilities. Foster et al [1988] using the Millstone Hill 440-MHz radar at angles of at least 11 ø away from the local magnetic field direction revealed echoes that could easily have been mistaken for satellite passes had they not had a consistent altitude profile and come from a fixed region of space.…”
mentioning
confidence: 99%
“…Rietveld et al (1991) presented a systematic study of NEIALs received by the EISCAT UHF system. Several models to explain NEIALs have been proposed such as the current driven instability (Foster et al, 1988) and the ion-ion twostream instability (Wahlund et al, 1992). To decide whether and how the cross section of NEIALs depends on the wave vector k may enable us to distinguish between such instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Rietveld et al (1991) presented a systematic study of NEIALs received by the EISCAT UHF system. Several models to explain NEIALs have been proposed such as the current driven instability (Foster et al, 1988) and the ion-ion twostream instability (Wahlund et al, 1992). To decide whether and how the cross section of NEIALs depends on the wave vector k may enable us to distinguish between such instabilities.…”
Section: Introductionmentioning
confidence: 99%